2019
DOI: 10.1371/journal.pone.0216886
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Ethiopian Capsicum germplasms

Abstract: We established a collection of 142 Capsicum genotypes from different geographical areas of Ethiopia with the aim of capturing genetic diversity. Morphological traits and high-resolution melting analysis distinguished one Capsicum baccatum , nine Capsicum frutescens and 132 Capsicum annuum accessions in the collection. Measurement of plant growth parameters revealed variation between germplasms in parameters including pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 54 publications
5
24
0
Order By: Relevance
“…Genomic DNA was extracted from the samples using the CTAB method ( Lee et al., 2017 ; Siddique et al., 2019 ; Solomon et al., 2019 ) and diluted to 80 ng/µl in distilled water. GBS libraries were constructed via double digestion with two sets of restriction enzymes ( Pst I/ Mse I and EcoR I/ Mse I) as previously described ( Han et al., 2018 ; Siddique et al., 2019 ; Solomon et al., 2019 ). The digested DNA was ligated to adapters and amplified with ‘TA’ primers.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from the samples using the CTAB method ( Lee et al., 2017 ; Siddique et al., 2019 ; Solomon et al., 2019 ) and diluted to 80 ng/µl in distilled water. GBS libraries were constructed via double digestion with two sets of restriction enzymes ( Pst I/ Mse I and EcoR I/ Mse I) as previously described ( Han et al., 2018 ; Siddique et al., 2019 ; Solomon et al., 2019 ). The digested DNA was ligated to adapters and amplified with ‘TA’ primers.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation of diversity is relevant for broadening the genetic base for identi cation of bene cial alleles for improvement of current germplasm [24]. A GBS approach was used for SNP marker discovery and to examine genetic diversity, population structure, and linkage disequilibrium among a diverse New Mexican Capsicum population.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity, which represents the magnitude of genetic variability within a population, is an important source of biodiversity [23] and is relevant for association studies, genomic selection, and individual identi cation, and is crucial to the overall success of plant breeding programs [24,25]. Diversity in plant genetic resources provides avenues for plant breeders to develop novel varieties with improved characteristics such as yield potential, pest and disease resistance, and productivity [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis based on molecular markers, pan-genome sequencing, and GBS confirmed that C. chinense and C. frutescens are more closely related to each other than to C. annuum [29, 61, 64]. Several studies attempted to characterize the population relatedness of cultivated C. annuum in restricted geographical areas [29, 36, 40–42, 65]. They revealed that the population structures of the C. annuum accessions were mainly associated to distinct cultivar types with respect to the plant and fruit descriptors, and thus mostly result from human selection for cultivar types in agreement with consumption modes and adaptation to the highly diversified agro-climatic conditions.…”
Section: Discussionmentioning
confidence: 99%